The Influence of Organizational Factors to Software-As-A Service (SAAS) Adoption in Vietnamese Enterprises - Le, Thi Thu Ha (H. : ĐHQGHN, 2020)
With the growth of the information technology industry, the literature exploring cloud computing, in particular, SaaS adoption has been developing considerably over the last few years. It is time to take stock of SaaS adoption’s determinant factors and its application to more specific contexts. This study endeavored to investigate the influence of three organizational factors (organizational size, organizational readiness, and top management support) to SaaS adoption in Vietnamese enterprises across sectors. Qualitative method was employed to analyze data gathered from 18 case-study companies. The findings reconfirmed that top management support is the strongest enabler for SaaS adoption while there are still some contradictions between organizational size as well as organizational readiness versus SaaS adoption in the context of a developing country as Vietnam.